Algebra and Logics - Bhusal, Tika Ram (Journal of Institute of Science and Technology, 2015)
The context of abstractness in Algebra depends on the study of logics. Logics when dealt in some meaningful way may give challenges to the game of theories and theorems. We have tried to find some examples which should be with the spirit of trends of thoughts. Axioms are basic assumptions but they should be consistent throughout the problem. In the study of logics, statements should satisfy certain property. We cannot introduce any statement in the curriculum dictatorially. Journal of Institute of Science and Technology, 2014, 19(2): 142-144